The Evolving landscape of Antibiotic resistance: A state-by-state Perspective and Mapping of Antibiotic resistance Hotspots in India - Sumitha J,; Priyalakshmi S,; Yamunakshri R, (The Bioscan, 2024)
Antibiotic resistance is a serious concern of developing countries like India and is expected to hit its rockbottom.Antimicrobial resistance (AMR) is one of the top global public health and development threats. It is estimated that bacterial AMR was directly responsible for 1.27 million global deaths in 2019 and contributed to 4.95 million deaths Priorities to address AMR in human health include preventing all infections, which may result in inappropriate use of antimicrobials; ensuring universal access to quality diagnosis and appropriate treatment of infections; and strategic information and innovation, for example surveillance of AMR and antimicrobial consumption/use, and research and development for novel vaccines, diagnostics and medicines.(WHO, November 2023).Surveillance of AMR plays a pivotal role in research and helps us to steer the course of AMR against the setbacks in modern medicine and treatment better.This paper reviews meticulously the evolving landscape of Antibiotic resistance and Mapping of Antibiotic resistance Hotspots in India from before COVID for a period of four years 2015 to 2019 and after covid 2020 to 2024.